2012
DOI: 10.2337/dc11-1511
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Parkinson Disease Onset in Patients With Diabetes

Abstract: OBJECTIVEWe retrospectively assessed the age- and sex-specific incidence and relative risk of Parkinson disease (PD) in Taiwan’s diabetic population.RESEARCH DESIGN AND METHODSStudy cohort included 603,416 diabetic patients and 472,188 nondiabetic control subjects. Incidence rate and relative risk of PD (ICD-9-CM 332.0) were evaluated.RESULTSThe incidence of PD was 3.59 and 2.15 per 10,000 person-years for the diabetic and control group, respectively, representing a covariate adjusted hazard ratio (HR) of 1.61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
132
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(135 citation statements)
references
References 14 publications
2
132
0
1
Order By: Relevance
“…Cohort studies have suggested that patients with diabetes are at a higher risk of PD [26,27,28]. In experimental animal studies, chronic hyperglycemia reduced striatal dopaminergic transmission and enhanced the sensitivity of postsynaptic dopamine receptors [29].…”
Section: Discussionmentioning
confidence: 99%
“…Cohort studies have suggested that patients with diabetes are at a higher risk of PD [26,27,28]. In experimental animal studies, chronic hyperglycemia reduced striatal dopaminergic transmission and enhanced the sensitivity of postsynaptic dopamine receptors [29].…”
Section: Discussionmentioning
confidence: 99%
“…PD is diagnosed by characteristic motor impairments (Langston, 2002), caused by a reduction in striatal dopamine levels, which is due to the loss of dopaminergic neurons in the substantia nigra (Moore et al, 2005;Wakamatsu et al, 2008). Importantly, type 2 diabetes (T2DM) has been identified as a risk factor for PD (Hu et al, 2007;Schernhammer et al, 2011;Sun et al, 2012;Wahlqvist et al, 2012). Insulin signaling in the brain plays an important role in neuronal metabolism, repair, and synaptic efficacy (Freiherr et al, 2013;Ghasemi et al, 2013;van der Heide et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Additional factors such as BMI, alcohol use, coffee and tea consumption, smoking and physical activity did not alter this risk. Sun et al examined a study group in Taiwan composed of 600,314 diabetic patients and 472,188 non-diabetic patients and evaluated the risk of developing PD for 9 years [41]. The number of PD onset per 10,000 people was 3.59 in the DM group per year and 2.15 in the non-DM group, representing a covariate adjusted hazard ratio of 1.61.…”
Section: Resultsmentioning
confidence: 99%